Funcionamiento cognitivo en preescolares con desnutrición del cantón Macará - Vélez Elizalde, Carolina Alexandra (2022)
Malnutrition in the first years of life constitutes a risk factor in the manifestation of alterations in intellectual development and consequently can decrease the capacity of cognitive function, since the prenatal stage and childhood are considered determinant periods with respect to the psychological development. The purpose of this research was to determine the relationship between cognitive functioning and malnutrition in preschoolers in the Macará canton. The study was carried out with a quantitative approach, of a non-experimental design with a cross section and the type of research was descriptive and correlational, in which 57 preschool children with malnutrition between 6 and 36 months of age participated, the same ones that were selected using the technique non-probability sampling for convenience. The Battelle Development Inventory and the Database of users with malnutrition were used as instruments. The results indicated that there is an inverse correlation between cognitive functioning and malnutrition, therefore the correlation between variables is not statistically significant, that is, malnutrition in early childhood is a factor to consider regarding cognitive retardation or normal development. Thus, the need arises to strengthen cognitive development in the child population through the execution of psychoeducational promotion and prevention plans, as well as the establishment of healthy habits in this vulnerable population